Residue Monitoring of Propiconazole in the Rice–Crab Co-Culture Field and its Toxicity and Bioaccumulation to Eriocheir sinensis - Yu, Lina; Li, Changsheng; Zhang, Yuting; Guo, Xuanjun; Cao, Niannian; Guo, Shuxin; Wu, Sijia; Li, Xuefeng; Pang, Sen (Frontiers in Environmental Science, 2022)
Rice-crab co-culture is a high-benefit ecobreeding pattern that has been extensively developed in many regions of China. However, little attention has been paid to the safety of pesticides used to control rice pests in crab-rice co-culture system. This study monitored the actual residue levels of propiconazole in the water and soil of rice-crab co-culture fields, and evaluated the acute toxicity, subchronic toxicity and bioaccumulation of propiconazole to Eriocheir sinensis. We observed that the residue level of propiconazole in paddy soil was higher than that in paddy water within 42-day field monitoring. Propiconazole demonstrated a low acute toxicity (96h-LC50 > 100mg/L) to E. sinensis, and exhibited no obvious adverse impact on the growth of E. sinensis after exposure to 500µg/L, which was 10 times the actual residual concentration of propiconazole in crab-rice co-culture field. Highest bioaccumulation of propiconazole were obtained from gills, followed by hepatopancreas and meat. These results will contribute to the guidance of scientific utilization of pesticides in crab-rice co-culture field.